(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
his study aims to identify the potency of bioactive compounds of sweet potato leaf as inhibitory agent to dengue virus (DENV) NS2B/NS3 protease by using computational study. The 3D structure of NS2B/ NS3 protease was collected from PDB and the 2D structure of several bioactive compounds of sweet potato leaf were obtained from PubChem. The visualization and data analysis were performed by using the PyMol software. According to the in silico analysis, result demonstrated that dehydroabietinol had the lowest free energy binding. However, based on the protein-ligand analysis, all the compounds showed the hydrogen bond and hydrophobic interaction. All the compounds with hydrogen bond could not be interacted with catalytic domain, but hydrophobic interaction could be interacted to the target domain via Ser135 by ?-Selinene and His51 by ?-Caryophyllene. In summary, we conclude that ?-Selinene and ?-Caryophyllene might have potencies as a therapeutically drug for dengue.